Strategi dan Evaluasi Meningkatkan Keterampilan Berpikir Kreatif: Systematic Literature Review - Maryam, Eka; Jufri, Jufri; Romadon, Romadon; Yani, Nurul Ari; Fahrudin, Ahmad (STKIP ROKANIA, 2023)
Teaching and evaluation strategies greatly influence success in fostering students' creative thinking abilities. The objectives of this study are to (1) examine various literature on creative thinking; (2) examine various indicators of creative thinking skills; (3) investigate various teaching strategies to improve creative thinking skills and their evaluation instruments. The research method used is descriptive research with a qualitative approach. The data in the study is in the form of secondary data in the form of research journals that examine the scope of students' creative thinking. Data analysis techniques use Miles and Huberman's model, namely data collection, data reduction, data presentation, and conclusion drawing. The number of articles found was 117 articles using the help of journal indexers such as Scopus, google scholar, Eric, and DOAJ. This study decided to review 36 articles based on the results of data reduction carried out from 117 articles. The conclusion of this study is that studying various proven theories and applying them in the classroom is the most appropriate step as a strategy to improve students' creative thinking skills. These strategies include active learning models such as: based learning projects, cooperative learning, problem based learning, and discovery/ based inquiry.